Rapid gas recognition function-based curtain - LIN YECHENG (2016)
The invention discloses a rapid gas recognition function-based curtain. A detection device is arranged on the sunny surface of the curtain, wherein the detection device is based on a self-powered sensing element and also comprises a data reading module a gas recognition module; the self-powered sensing element comprises a dye-sensitized solar cell module and a gas sensor module; and the dye-sensitized solar cell module can achieve the function of gas detection when supplying power by solar energy as a working power supply of the gas sensor module. The rapid gas recognition function-based curtain is high in sensitivity and high in repeatability, and greatly expands the application range of the curtain. 本发明公开了一种基于快速气体识别功能的窗帘，通过在窗帘的向阳表面安装检测装置，该检测装置基于自供能感测元件，并且还包括数据读取模块和气体识别模块；自供能感测元件包括染料敏化太阳能电池模块和气体传感器模块，染料敏化太阳能电池模块作为气体传感器模块的工作电源，可以利用太阳能供电同时实现检测气体的功能，并且灵敏度高，重复性高，大大扩展了该窗帘的适用范围。